Preparation of nano-structured Ag solid materials and application to surface-enhanced Raman scattering - Yi, Zao; Chen, Yan; Chen, Shan-jun; Tan, Xiu-lan; Niu, Gao; Luo, Jiang-shan; Tang, Yong-jian; Yi, You-gen (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2011)
Silver nano-particles with average diameter of about 60 nm were compacted in a high-strength mold under different pressures at 523 K to produce nano-structured Ag solid materials. The structure and characteristic of the nano-structured Ag solid materials (NSS-Ag) were studied using X-ray diffraction (XRD), scanning electron microscope (SEM) and Raman spectrometer. The NSS-Ag could be used as highly efficient surface-enhanced Raman scattering (SERS) active substrates. The common probe molecules Rhodamine 6G (R6G, 1×10 −10 mol/L) were used to test the SERS activity on these substrates at very low concentrations. It is found that the SERS enhancement ability is dependent on the density of NSS-Ag. When the relative density of NSS-Ag is 83.87%, the materials reveal great SERS signal.